1999
DOI: 10.2223/jped.295
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax malaria in children and adolescents - epidemiological, clinical and laboratory features

Abstract: Objective: Evaluation of epidemiological, clinical and laboratory features of Plasmodium vivax malaria in children and adolescents.Methods: This study was carried out in the Malaria Program of the Evandro Chagas Institute (Belém, Pará), from January 1995 to November 1996. 100 children and adolescents with the diagnosis of P. vivax malaria (thick blood film) were randomly enrolled. A protocol was created to assess epidemiological, clinical and laboratory parameters of this pathology.Results: Malaria occurred in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Severe complications of P. vivax infections have been reported consistently in the past years in South America and in other regions of the globe (35,40,60,61). A study focused on children (0 to 14 years old) infected by P. vivax conducted in Belém, the same locality in which we performed part of this study, showed that the vast majority (82.7%) of the patients were anemic (68). These studies referred to hospitalized patients and/or specific groups such as children and provide no information on the prevalence of such complications in the populations in which they occur.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Severe complications of P. vivax infections have been reported consistently in the past years in South America and in other regions of the globe (35,40,60,61). A study focused on children (0 to 14 years old) infected by P. vivax conducted in Belém, the same locality in which we performed part of this study, showed that the vast majority (82.7%) of the patients were anemic (68). These studies referred to hospitalized patients and/or specific groups such as children and provide no information on the prevalence of such complications in the populations in which they occur.…”
Section: Discussionmentioning
confidence: 77%
“…Although infections by these two species have been considered to be very different, with quite different biological and pathophysiological characteristics, the leveling factor likely is the early phase of the infection at which patients were enrolled in the study, when they looked for health care soon after the first symptoms appeared. In addition, age must have a strong influence, since we dealt mostly with adults, and previous works in this region and in regions with similar epidemiological characteristics showed that children are unequivocally more vulnerable to malaria complications, whether from P. vivax or P. falciparum infection (19,41,68).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dengue in children living in areas in the N Region [141,142], CO Region [145] and SE Region [147] have led to a disruption of routine health services, demanding further efforts towards providing technical training to health professionals working on the frontline of dengue treatment in children's patient care. As for malaria, researches had investigated children and adolescents who live in the N region [151,152]. The lethality was 1.6% and besides the common symptoms of malaria triad (fever, chills and headache) they had among others like pallor, anemia, myalgia, vomiting and some degree of malnourishment [151], and there was a prevalence of malaria among adolescents [152].…”
Section: Grandjean Et Almentioning
confidence: 99%
“…As for malaria, researches had investigated children and adolescents who live in the N region [151,152]. The lethality was 1.6% and besides the common symptoms of malaria triad (fever, chills and headache) they had among others like pallor, anemia, myalgia, vomiting and some degree of malnourishment [151], and there was a prevalence of malaria among adolescents [152].…”
Section: Grandjean Et Almentioning
confidence: 99%
See 1 more Smart Citation